Analyse psychosociale et critique d’un dispositif participatif de promotion à la santé sexuelle - Marwa Mahmoud; Nathalie Muller Mirza (Communication)
With this article, we seek to contribute to critical reflections on power relationships at different levels — interpersonal, institutional and political — of participatory practices referred to as “inclusive”. Based on the analysis of a sexual health promotion project targeting Muslim communities in Switzerland, we highlight a paradox between the intention to include a population considered to be a minority and the othering mechanisms in communications between the various players in the project. By adopting a sociocultural and dialogical approach to psychology and a comprehensive methodology combining document analysis, semi-directive interviews, participant observations and the identification of critical incidents, we look at the psychosocial dynamics emerging among the different actors involved in the project and highlight the hiatus that we call “dialogical tensions” between the different perspectives. Our results show that othering processes are at work and involve the entire project, from its design to its implementation during training workshops. The study thus helps to shed light on some of the mechanisms that maintain power relations in interactions within a participatory project.